Physical and Numerical Modeling of the Stability of Deep Caverns in Tahe Oil Field in China - Chao Wang; Qiangyong Zhang; Wen Xiang (Energies, 2017)
Cave collapses emerge during the process of oil reservoir development, seriously affecting oil production. To reveal the collapse and failure mechanism of the carbonate cavern with a buried depth of 5600 m in Tahe Oil Field, using a self-developed ultra-high pressure model test system with the intelligent numerical control function, the model simulation material of carbonate rocks developed to carry out the 3D geo-mechanical model test. The model test and numerical results indicate that: (1) collapse and failure mechanism of the deep-buried caves mainly involve the failure mode of tensile shear. The rupture plane on the side wall is approximately parallel to the direction of maximum principal compressive stress. The V-type tension and split rupture plane then emerges. (2) In the process of forming holes in the model caverns, micro cracks are generated at the foot of the left and right side walls of the caverns, and the roof panels are constantly moving downward. The shorter the distance to the cave wall, the severer the destructiveness of the surrounding rocks will be. (3) The displacement of the top of the model cavern is relatively large and uniform, indicating that the cave roof moves downward as a whole. The area of the cavity suffering damage is 2.3 times as large as the cave span. The research results in this paper lay a solid test basis for revealing the cave collapse and failure mechanism in super depth.